(untitled) (Journal of the College of Education for Women, 2019)
Some degree of noise is always present in any electronic device thattransmits or receives a signal . For televisions, this signal i has been to s thebroadcast data transmitted over cable-or received at the antenna; for digitalcameras, the signal is the light which hits the camera sensor. At any case, noiseis unavoidable. In this paper, an electronic noise has been generate onTV-satellite images by using variable resistors connected to the transmitting cable. The contrast of edges has been determined. This method has been applied bycapturing images from TV-satellite images (Al-arabiya channel) channel withdifferent resistors. The results show that when increasing resistance alwaysproduced higher noise for a television image .